Histone deacetylase inhibitor (HDACi) upregulates activin A and activates the Smad signaling pathway in melanomas. Issue 1 (April 2018) - Lee, Jeeyong; Ko, Jiwon; Yi, Jae Youn
Highlights: SAHA treatment inhibited melanoma cell proliferation. Conditioned medium from SAHA-treated SK-Mel-5 cells enhanced Smad signaling pathway. Activin A could be a key constituent of the SAHA-treated conditioned medium. Abstract: Background: Histone deacetylase (HDAC) is an enzyme that regulates gene expression, cell cycle arrest, apoptosis and modulation of various pathways. HDAC inhibitors (HDACis) can modulate these pathways by hyper-acetylating target proteins, thereby acting as cancer chemotherapeutic agents. Objective: One of HDACis, suberoylanilide hydroxamic acid (SAHA), has been found to regulate the Smad signaling pathway, by an as yet unclear mechanism. This study therefore investigated the mechanism by which SAHA regulates Smad signaling in the melanoma cell line SK-Mel-5. Methods: Cell proliferation was assessed by MTT assays and fluorescence activated cell sorter (FACS) analysis. The activation of Smad signaling pathway was assessed by western blots analysis. The transcriptions of target genes were checked by RT-PCR and dual luciferase assay. Results: Treatment with SAHA inhibited the proliferation of SK-Mel-5 cells, enhanced the phosphorylation of R-Smad, and up-regulated p21 protein. Surprisingly, R-Smad was also activated by conditioned medium from SAHA-treated SK-Mel-5 cells. An analysis of the conditioned medium showed that activin A was responsible for the activation of R-Smad. SAHA treatment enhanced the level of activin A mRNA, increasing the level of activin A in the secretome. The activity of the SAHA-treated secretome could be eliminated by pre-incubation with antibody to activin A. In addition, activin A supplemented medium could mimic the effect of the SAHA-treated secretome. Conclusion: These findings indicate that the anti-cancer function of SAHA is mediated, at least in part, by the upregulation of activin A.